Asymmetric Cointegration, Nonlinear ARDL, and the J-Curve: A Bilateral Analysis of China and Its 21 Trading Partners. Issue 13 (21st October 2018) - Bahmani-Oskooee, Mohsen; Bose, Niloy; Zhang, Yun
ABSTRACT: This article follows the nonlinear Autoregressive Distributed Lag (ARDL) error-correction methodology to explore nonlinearity in the relationship between the trade balances and the real exchange rates for China and its 21 partners. We find evidence for short-run asymmetric effects of exchange rate in cases of 18 partners, short-run adjustment asymmetry in cases of 11 partners, short-run cumulative asymmetry in cases of seven partners, and a significant long-run asymmetric effect cases of five partners. We find support for the "J-curve" that is only due to appreciation or depreciation of the Yuan in cases of five partners, including the U.S.